PENATALAKSANAAN FISIOTERAPI PADA OSTEOARTHRITIS GENU DEXTRA SHORT WAVE DIATHERMY, TRANSCUTANEOUS ELECTRICAL NERVE STIMULATION, DAN TERAPI LATIHAN PADA OSTEOARTHRITIS GENU DEXTRA - Khusniyati, Arini; Amanati , Suci (Universitas Pembangunan Nasional Veteran Jakarta, 2023)
Background: Genu Osteoarthritis is a chronic degenerative disease and the exact cause is unknown. Genu OA is influenced by age, gender, weight and genetic. Because these factors are more likely to put a load or pressure on the knee joint as a means of locomotion. The problems experienced by patients are weakness or disorders such as pain, muscle spasm, decreased muscle strength values and impaired activity and functional abilities. The purpose of writing this scientific paper is to find out the Physiotherapy Management of Osteoarthritis Genu Dextra with Short Wave Diathermy, Transcutaneous Electrical Nerve Stimulation and Exercise Therapy. Method: This scientific paper is a case study, taking the patient's case and collecting data through the physiotherapy process. The modalities given are Short Wave Diathermy, Transcutaneous Electrical Nerve Stimulation and Exercise Therapy. Results: After four times of physiotherapy, the results showed a reduction in the degree of pain, spasm, increased muscle strength values and increased functional ability of patient activities. Conclusion: Short Wave Diathermy, Transcutaneous Electrical Nerve Stimulation and Exercise Therapy given to patients can help reduce pain, reduce spasm, increase muscle strength values and increase the functional ability of patient activities. Keywords: Oateoarthritis Genu Dextra; SWD; TENS; and Exercise Therapy